Seroprevalence of Nipah virus and related paramyxoviruses in native frugivorous bats, Luzon, Philippines - Rekedal MS; Noroña M-G; Café JAP; Mittal N; Borthwick SA; Taray KJ; Garcia JJL; Magsanoc SL; Cruz HR; Manzano DJ; Yan L; Low DHW; et al. (Taylor and Francis Group on behalf of hanghai Shangyixun Cultural Communication Co, LTD, 2025)
Nipah virus (NiV) is a highly virulent zoonotic virus classified as a priority pathogen and biohazard. In 2014, an outbreak of NiV-like disease in the Province of Sultan Kudarat, Mindanao, Philippines resulted in a 53% case fatality rate. Here, we identified wildlife bat hosts of NiV by conducting monthly serological surveillance of flying foxes and other native frugivorous bat species across Luzon. We estimated 13.92% NiV seroprevalence in native flying foxes. We also detected NiV neutralizing activity in some flying fox sera and identified factors such as age and seasonality as drivers of high anti-NiV antibody levels. In contrast, less than 10% NiV seroprevalence was detected in R. amplexicaudatus, C. luzoniensis, and P. jagori bats, and these bats have no detectable neutralizing antibodies. This is the first serological description of NiV in native flying foxes in the Philippines, highlighting a major wildlife host in an understudied region.
Keywords: Nipah virus; bats; Philippines; biosurveillance; spill over risk